Kepemimpinan dan Kompensasi terhadap Kinerja Pegawai Nonmedis Rumah Sakit - Fitria Fitria; Suyadi Suyadi; Hery Hery (IPM2KPE, 2022)
This study aims to determine the effect of leadership, compensation, and the two factors (leadership and compensation) on the performance of non-medical employees of Dr. Hospital. Sobirin, Musi Rawas Regency. The research method used is a quantitative method. Data collection methods in the form of observation, questionnaires, and documentation. The results showed that the results of the T test on the leadership variable showed the tcount value was greater than ttable, namely 1.933 > 0.679 with dk = 60 (60-3) and the significant level was 0.058. The compensation variable shows the value of tcount is greater than ttable, namely 3.373 > 0.679 with dk = 60 (60-3) and the significant level of sig is 0.001. The fcount value of = 9.117 is greater than the ftable value = 3.17 and the probability (sig. 0.004). In conclusion, partially leadership and compensation variables, and simultaneously leadership and compensation variables have a partial and significant effect on the performance of non-medical employees at Dr. Hospital. Sobirin, Musi Rawas Regency. Keywords: Leadership, Employee Performance, Compensation